2005
DOI: 10.5424/sjar/2005031-132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of row spacing and lineal sowing density of kenaf (Hibiscus cannabinus L.) yield components in the North-West of Argentina

Abstract: The plant density and spatial arrangement of kenaf is an important aspect in kenaf fiber production. A field plant density experiment was conducted at Ledesma (Jujuy, Argentina) in 2001 on a sandy loam soil. The treatments used were different combinations of 35 and 70 cm row spacings with lineal sowing densities of 25 and 40 plants m-1, and were applied to the Cuba 108, Endora and Tainung 1 cultivars. Two indices (bark content and bark index) related to fiber yield and useful for the individual selection of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The main changes occurred when plant density was between 160,000 and 840,000 plants ha −1 Plant height was not affected by population density. Reductions in stem diameter due to population density increases are similar to those found in other studies, resulting from intraspecific competition among plants (Campbell and White, 1982; Acreche et al, 2005). As for the LAI, only in the first year was a positive linear relationship with plant population observed, with an increase rate of 0.157 per 100,000 plants ha −1 In 2006, LAI ranged from 3.6 to 4.0 (Fig.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The main changes occurred when plant density was between 160,000 and 840,000 plants ha −1 Plant height was not affected by population density. Reductions in stem diameter due to population density increases are similar to those found in other studies, resulting from intraspecific competition among plants (Campbell and White, 1982; Acreche et al, 2005). As for the LAI, only in the first year was a positive linear relationship with plant population observed, with an increase rate of 0.157 per 100,000 plants ha −1 In 2006, LAI ranged from 3.6 to 4.0 (Fig.…”
Section: Resultssupporting
confidence: 87%
“…Little information is available regarding kenaf forage response to population density, which affects plant morphology, dry matter (DM) accumulation, and susceptibility to lodging. Previous research has focused primarily on the effect of population density on stem and total DM yield for fiber production (Campbell and White, 1982; Acreche et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to produce kenaf crop as a commercial crop on a large scale in Iraq, many scientific information about its production need to be known like plant population and nitrogen fertilizer recommendations. Acreche et al (2005) in Argentine found that combination of 35 cm row spacing and 25 plants/m lineal density of 714286 plants/ha, resulted in the best dry bark yield. Between the two plant population used by Alexopoulou et al, (2000),showed that the high plant population (320000 plant/ha) was more productive than the low one (170000 plant ha -1 ) but this difference was statistically significant only until flowering phase .…”
Section: Introductionmentioning
confidence: 99%